Restoration of abandoned agricultural lands toward umbrella species habitats - Nekhay, O.; Arriaza, M. (Instituto Nacional de Investigación y Tecnología Agraria y Alimentaria (España), 2009)
This study analyzes the suitability of agricultural lands with risk of abandonment for restoration to suitable habitats for animal species of conservation interest. As a case study, the main focus was on olive plantations of mountainous areas of Southern Spain and the Iberian lynx. The method weighs the judgement of experts on the effect of landscape elements on the habitat via an analytic hierarchy process and spots areas most suitable for restoration through geographical information systems. The precise location of olive groves suitable for restoration are discussed, as revealed by experts decision-making processes. The main interest of the study relies on the potential of the method to combine territorial analysis with biological requirements of endangered species to facilitate their dispersal. El trabajo analiza las zonas de olivar de montañas más adecuadas para la restauración del hábitat del lince ibérico. La metodología incluye el uso del Proceso de Análisis Jerárquico (AHP) y los Sistemas de Información Geográfica (SIGs). El estudio combina el análisis territorial con los requerimientos biológicos de una especia en extinción para su dispersión.